The Achievement and Satisfaction on Machine Elements Subject using SolidWorks Program - ชูเมฆา อภิรมย์; ชูเมฆา ดลหทัย (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2017)
The purposes of this research were to study the achievement and satisfaction of students who study in industrial production program, RAJAMANGALA University of Technology, Thanyaburi toward learning machine elements by using instructional media (SolidWorks program). The experimental planning was one group pretest and posttest design. The sample consisted of 30 students (purposive sampling) who studied machine elements subject in the first semester, 2016 academic year. Achieve assessment and questionnaire were used for collecting data. Statistical methods included average, standard deviation and paired t-test were used to analyze data. The result revealed that learning achievement of students before and after using SolidWorks program were significantly difference at 1% significance level (p<0.01) and student satisfaction on SolidWorks program presented x ̅ (S.D.) approximately 4.60 (0.47) high at excellent level.